Simulation of various resonators as viscometer for engine oils - Tze, Ching Ong; Buja, Andy; Ak MawanSia, Dino Sabastian; Chee, Kiong; Yee, See Khee; Ong, Pauline (Politeknik Kuching Sarawak, 2020)
The viscometer is an instrument used to identify the resistance of a fluid to shear or tensile stress. Accurate characterization of viscosity is important in analyzing many engineering situations, especially in the automation industries, which consume engine oils that associate with the functionality or performance of vehicles and machinery. Therefore, this work aims to simulate various sensors via resonators before the fabrication process is performed. The viscosity is justified based on the variation of dielectric properties of the fluid. T-resonator shows the highest sensitivity in all designs with an S11 value of -54.212dB and DSRR with Roger 3003 performs the best in terms of Q-factor with 1883. This simulation results can be verified through experimentation as future works.